Negara Bangsa Dan Konflik Etnis: Nasionalisme vs Etno-Nasionalisme - Arrochman Mardiansyah (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
Ethnic conflicts are rooted from the way nation state deals with ethno-nasionalism. The disregard of ethno-nationalism in Indonesia helps us in explaining the current influx of ethnic conflicts.